Kecenderungan Perilaku Koruptif Kepala Desa dalam Pembangunan Desa - Dian Herdiana (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2019)
The commitment of the government in realizing village autonomy is realized by giving local-participatory development authority to the village. But in practice, the authority granted has been used by some village heads for corruption. On the basis of these problems, this article is intended to examine the causes of village heads to behave corruptly in the village development. This study uses a qualitative research method with an explorative approach, collecting data through observation and literature study. Data analysis techniques are carried out through data reduction, data presentation and conclusion. The results showed that the corrupt behaviour of the village head is caused by 3 (three) factors, namely: First, the regulatory factor in which the Villages Law gives a large development authority to the village government so that the position of the village head becomes a village-level central leader who monopolizes village development, coupled with the absence of village-level institutions that face-to-face to balances and controls the village head. Second, the personal factors of the village head such as the insistence of economic needs, greed, low integrity and morality as well as demands for political promises. Third, community factors in which there is no clear regulation/mechanism on how the community conducts monitoring and what indicators can be used as a reference by the community to assess the performance of the village head so that it has implications for the low level of community control over the village head. These three factors contributed greatly to the corrupt behaviour of village heads in village development.